COMPARATIVE ANALYSIS OF ORTHOPEDIC TRAUMA INTERVENTIONS: A REGISTRY-BASED STUDY ON TREATMENT OUTCOME - MEMON , MS; ISMAIL , H; SHAH , GA; RAHUJO , N; ZEESHAN , S; AHMED , T (Biological and Clinical Sciences Research Journal, 2023)
Musculoskeletal injuries represent a substantial public health challenge, significantly burdening healthcare providers and hospitals in developing nations. Efficiently managing the diagnosis and treatment of these injuries can result in cost savings in healthcare and a reduction in the duration of preventable disabilities among affected patients. This study aimed to analyze and compare the treatment outcomes of various orthopedic trauma interventions. In this retrospective cohort study conducted at the SMBB Institute of Trauma, a Tertiary Care Hospital, between January 2017 and December 2021, 4557 limb injuries sustained by 4557 patients were investigated. The study included patients with both upper and lower limb trauma. Detailed information regarding the injuries, trauma management strategies, and subsequent outcomes was meticulously extracted from the patient’s medical records. Data analysis was conducted using SPSS version 27 to uncover relevant patterns and insights in the management and outcomes of these limb injuries. A total of 4557 patients with 4557 limb injuries were enrolled in the study. The incidence of upper and lower limb injuries was 24.5% (n=1108) and 75.5% (n=3449), respectively. Surgical intervention was employed in 4191 (92%) cases, while the remaining 366 (8%) were managed conservatively. Open reduction and internal fixation (ORIF) were the most common surgical procedure performed, accounting for 1441 cases (34.4%), followed by Intramedullary Nailing with 491 cases (11.7%) and external fixation in 434 cases (10.4%). The overall mortality rate was 16 (0.35%), among which 10 cases were not associated with either the trauma itself or its management. The assessment of outcomes associated with injuries identifies potential areas of trauma care that require enhancement and suggests strategies to reduce the mortality rate. Registry data has the potential to aid in the formulation of preventative strategies and enhance the effectiveness of management protocols.